Characteristic features of ulcerative colitis with concomitant primary sclerosing cholangitis - Artur W. Uździcki; Marta Wawrzynowicz-Syczewska (Gastroenterology Review)
Ulcerative colitis is a chronic inflammatory bowel disease of the colon. The most frequent symptoms include bloody diarrhoea with rectal urgency and tenesmus. It is often complicated by the presence of primary sclerosing cholangitis, a chronic, cholestatic liver disease, characterised by the inflammation and fibrosis of bile ducts. The presence of primary sclerosing cholangitis seems to alter the course of ulcerative colitis, changing its natural course.